M011L-deficient oncolytic myxoma virus induces apoptosis in brain tumor-initiating cells and enhances survival in a novel immunocompetent mouse model of glioblastoma. Issue 8 (8th March 2016) - Pisklakova, Alexandra; McKenzie, Brienne; Zemp, Franz; Lun, Xueqing; Kenchappa, Rajappa S.; Etame, Arnold B.; Rahman, Masmudur M.; Reilly, Karlyne; Pilon-Thomas, Shari; McFadden, Grant; Kurz, Ebba; Forsyth, Peter A.
Abstract: Background: Myxoma virus (MYXV) is a promising oncolytic agent and is highly effective against immortalized glioma cells but less effective against brain tumor initiating cells (BTICs), which are believed to mediate glioma development/recurrence. MYXV encodes various proteins to attenuate host cell apoptosis, including an antiapoptotic Bcl-2 homologue known as M011L. Such proteins may limit the ability of MYXV to kill BTICs, which have heightened resistance to apoptosis. We hypothesized that infecting BTICs with an M011L-deficient MYXV construct would overcome BTIC resistance to MYXV. Methods: We used patient-derived BTICs to evaluate the efficacy of M011L knockout virus (vMyx-M011L-KO) versus wild-type MYXV (vMyx-WT) and characterized the mechanism of virus-induced cell death in vitro. To extend our findings in a novel immunocompetent animal model, we derived, cultured, and characterized a C57Bl/6J murine BTIC (mBTIC0309) from a spontaneous murine glioma and evaluated vMyx-M011L-KO efficacy with and without temozolomide (TMZ) in mBTIC0309-bearing mice. Results: We demonstrated that vMyx-M011L-KO induces apoptosis in BTICs, dramatically increasing sensitivity to the virus. vMyx-WT failed to induce apoptosis as M011L protein prevented Bax activation and cytochrome c release. In vivo, intracranial implantation of mBTIC0309 generated tumors that closely recapitulated the pathological and molecular profile of human gliomas. Treatment of tumor-bearing mice with vMyx-M011L-KO significantly prolonged survival in immunocompetent—but not immunodeficient—mouse models, an effect that is significantly enhanced in combination with TMZ. Conclusions: Our data suggest that vMyx-M011L-KO is an effective, well-tolerated, proapoptotic oncolytic virus and a strong candidate for clinical translation.